Titanium Dioxide as a Catalyst Support in Heterogeneous Catalysis - Samira Bagheri; Nurhidayatullaili Muhd Julkapli; Sharifah Bee Abd Hamid (The Scientific World Journal)
The lack of stability is a challenge for most heterogeneous catalysts. During operations, the agglomeration of particles may block the active sites of the catalyst, which is believed to contribute to its instability. Recently, titanium oxide (TiO2) was introduced as an alternative support material for heterogeneous catalyst due to the effect of its high surface area stabilizing the catalysts in its mesoporous structure. TiO2 supported metal catalysts have attracted interest due to TiO2 nanoparticles high activity for various reduction and oxidation reactions at low pressures and temperatures. Furthermore, TiO2 was found to be a good metal oxide catalyst support due to the strong metal support interaction, chemical stability, and acid-base property. The aforementioned properties make heterogeneous TiO2 supported catalysts show a high potential in photocatalyst-related applications, electrodes for wet solar cells, synthesis of fine chemicals, and others. This review focuses on TiO2 as a support material for heterogeneous catalysts and its potential applications.